Developing Online Fiduciary Registration System that is Strengthening Law and Justice - et al., Liana Endah Susanti (International Journal of Advanced Science and Technology, 2019)
Fiduciary guarantees that have long been known in Indonesia were originally one form of material guarantees based on jurisprudence and have not been clearly and comprehensively regulated in legislation. Along with the rapid development of the world of fiduciary guarantees among financing businesses and the banking world, the government issued Law No. 42 of 1999 concerning Fiduciary Assurance which is expected to be able to provide legal protection and legal certainty as well as justice for interested parties, as previously only based on jurisprudence in other words, it does not provide legal certainty. On 5 March 2013 through Circular Letter of the Director General of AHU Number AHU-06.OT.03.01 in 2013 imposed an Electronic Fiduciary Registration Administration System (Online System). The application of the Circular latter is intended to provide convenience (safe, comfortable, fast and clean) in the implementation of fiduciary collateral registration in lieu of the manual fiduciary registration system. Although this online fiduciary service has been implemented for a long time in Indonesia, so far there are still many polemics that have resulted in its ineffective and inefficient implementation. Departing from all these problems, normative juridical methods are very appropriate to use. This discussion is expected to be able to build an online fiduciary model by further developing better applications and services, and can answer all issues related to uncertain legal strength and guarantee justice for related parties.